Considerations on Forest Changes of Northwest China in Past Seven Decades - Guojing, Yang; Junhao, Li; Lihua, Zhou (Frontiers in Environmental Science, 2021)
Forests cover four billion hectares (31%) of the Earth’s landmass and contain over 75% of all carbon in vegetation. They provide renewable raw materials and natural amenities, protect land and water resources, harbor biological diversity and mitigate climate change. However, due to less precipitation, the forest coverage rate is only 5.86% in Northwest China. The forests in these arid areas are mainly distributed in alpine areas, which play a key role in runoff regulation and ensure the ecological and economic development of the middle and lower reaches of the inland basins. In the past several decades, China had experienced large-scale deforestation and reforestation. What were the changes of the few forest areas and growing stock in arid Northwest China? Has forest quality been restored? Changes of that had been analyzed in this paper. The results showed that forest area and growing stock decreased greatly from 1950s to 1970s; artificial forest area increased clearly and natural forests area stabilized from 1980s, and growing stock of forest per unit area was still lower than that in 1950s, the forest quality had not yet been restored. Results of the analysis of influencing factors showed that the policy-led human activities in different period were the efficient cause of forest changes in Northwest China. With the development of forestry science, more and more attention has been paid to forest ecological restoration. "Three-North Shelter Forest Program "(TNSFP)" in 1978 had made great progress on forest areas by afforestation, and the ecological benefits and economic benefits also increased remarkably owing to the increase artificial forest area. In recent years, great progress on forest areas has been made in afforestation, and the forests also contribute significantly to the ecology and economy. However, large-scale afforestation in Loess Plateau had caused a phenomenon of large investment and little effect on water conservation in some afforestation areas, which showed that afforestation initiated under different polices, which were not always scientifically based which resulted in unintended consequences. Clear ecological principles should be used to ensure best environmental and forest ecology outcomes.